2021
DOI: 10.35741/issn.0258-2724.56.1.18
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 Quarantine Influenced Online Exam Cheating: A Case of Bangladesh University Students

Abstract: This study aims to identify, through qualitative research, the influence of COVID-19 on student online exam cheating, specifically e-cheating, during the COVID-19 quarantine in Bangladesh university online classes in 2020. The researcher obtained the primary data from 23 undergraduate university students (13 males and ten females) who willingly responded to a semi-structured interview via Messenger Interview. Using grounded theory analysis, the author found that quarantine during the COVID-19 pandemic has caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The Covid-19 pandemic, which has been going on for about a year, demands that learning be carried out online. Through their research, Churiyah, Sholikhan, Filianti, and Sakdiyyah (2020) and Abdelrahim (2021) state that this online learning system is a psychological challenge for teachers and students. On the one hand, teachers are required to convey lesson materials as clearly as possible so that all students are able to receive them well.…”
Section: Introductionmentioning
confidence: 99%
“…The Covid-19 pandemic, which has been going on for about a year, demands that learning be carried out online. Through their research, Churiyah, Sholikhan, Filianti, and Sakdiyyah (2020) and Abdelrahim (2021) state that this online learning system is a psychological challenge for teachers and students. On the one hand, teachers are required to convey lesson materials as clearly as possible so that all students are able to receive them well.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions on teaching activities. More than half of the students say that exams are easy to pass in online education, compared to onsite education, due to the lack of proctoring (Reedy et al, 2021), the opportunity to communicate with classmates, the availability of course material or easy access to online informational resources without being penalized since it is almost impossible to prove online cheating (Bilen & Matros, 2021), the opportunity to obtain a better grade (Abdelrahim, 2021;Dendir & Maxwell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Abdelrahim (2021) found that the factors that contribute to online cheating include stress, anxiety, depression, loneliness, the feeling of helplessness, social distancing, social isolation, peer and academic pressure, lack of understanding of course materials, lack of independent learning, not using software that monitors e-cheating, lack of monitoring, willingness to get a high and best grade, finding it is easy to cheat, and worries about jobs.…”
Section: Educational Factorsmentioning
confidence: 99%